(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article discusses the issues of sports training of women (boxers). The data of the analysis of studies of various aspects of preparedness (physical, technical, tactical, functional) are presented. The features of competitive activity of female boxers are studied. The actual problems requiring theoretical and practical substantiation of the rational construction of the training process of women (boxers) are identified